2020
DOI: 10.1002/cti2.1134
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/Rho‐kinases in asthma: from pathogenesis to therapeutic targets

Abstract: Asthma is a chronic and heterogeneous disease characterised by airway inflammation and intermittent airway narrowing. The key obstacle in the prevention and treatment of asthma has been our incomplete understanding of its aetiology and biological mechanisms. The ras homolog family member A (RhoA) of the Rho family GTPases has been considered to be one of the most promising and novel therapeutic targets for asthma. It is well known that RhoA/Rho-kinases play an important role in the pathophysiology of asthma, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 114 publications
0
36
0
Order By: Relevance
“…Another possible contributor is RhoA, a TGF-β–inducible molecule that was highly expressed in pediatric AMs in our study and has been implicated in macrophage polarization and function. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Another possible contributor is RhoA, a TGF-β–inducible molecule that was highly expressed in pediatric AMs in our study and has been implicated in macrophage polarization and function. 45 …”
Section: Discussionmentioning
confidence: 99%
“…To further address the relative contribution of AhR in the activation of the TGFβ1/Smad3 signaling axis, we studied its underlying mechanisms by focusing on RhoA/Rho-kinase signaling. RhoA is a nucleotide-dependent protein, switching between an inactive form, GDP-bound RhoA, and an active form, GTP-bound RhoA, and has been shown to regulate various biological functions, including cell differentiation, differentiation, recruitment, and apoptosis (37,57,58). Increased expression and activation of RhoA have been associated with asthma (59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…mechanisms regarding the regulation of TGFβ1 signaling, which may provide novel insights into the mechanisms that lead to allergic airway inflammation. The ras homolog family member A (RhoA) of the Rho family GTPases has been considered to be one of the most promising and novel therapeutic targets for asthma (37). Studies including ours have suggested a positive loop between RhoA/Rho-kinase signaling and TGFβ1 that drives airway constriction, airway hyper-responsiveness, and airway remodeling in asthma (38)(39)(40)(41), raising the possibility that RhoA/Rho-kinase signaling may be one of the central pathways in regulating allergen-induced TGFβ1 activation.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α, IL-13, IL-4, IL-17A and CCL2 are found to increase RhoA mRNA expression via NF-κβ and STAT6 signaling pathways activation, leading to airway hyperreactivity in asthma. Activation of TGF-β1 also has a key role in hASM contraction by increasing RhoA/ROCK-medicated phosphorylation of myosin phosphatase targeting subunit 1 (MYPT1) and myosin light chain (MLC) through PI3K signaling pathway activation [ 97 ].…”
Section: In Vitro Effects Of Nicotine On Asthma Developmentmentioning
confidence: 99%